Retained Foreign Body in the Pleura - Jana, Pulak Kumar; Das, Sibes Kumar; Bandyopadhyay, Rajat; Bairagya, Tapan Das (Journal of Medicine, 2011)
DOI: http://dx.doi.org/10.3329/jom.v12i2.6972 JOM 2011; 12(2): 191